Insuficiencia de políticas públicas que garanticen la tutela judicial efectiva en los casos de infracciones de violencia intrafamiliar en el ámbito psicológico cuando el sujeto pasivo es el hombre. - Uchuari Puglla., Viviana Patricia (2025)
This curricular integration work focuses on the issue of domestic violence against men in Ecuador, highlighting the weaknesses in the legal framework and public policies that have mostly been oriented towards protecting women. Through interviews with legal specialists and surveys of male victims, the barriers that men face when trying to access justice are identified, and guidelines are proposed to improve their situation. One of the most significant findings is that the current legal system does not adequately guarantee the protection of the rights of men who suffer psychological or physical violence at home. Weaknesses in the legal framework contribute to the impunity of these acts, which in turn affects the mental health of victims. The need for sociocultural change is emphasized to allow men to be seen not only as aggressors but also as potential victims, promoting impartial education from childhood. The work proposes several specific objectives, including the need to present proactive guidelines to enhance public policies that guarantee effective judicial protection in cases of domestic violence against men. To this end, comprehensive training of prosecutors, police officers, and judges is suggested, in order to break gender stereotypes and improve the handling of these cases. The creation of specialized units in judicial institutions is another key recommendation, ensuring that there is an adequate and sensitive approach towards male victims. Furthermore, the importance of developing comprehensive protection programs that include shelters adapted to men's needs, as well as awareness campaigns that educate the population about domestic violence in all its forms, is proposed. These initiatives seek not only to improve access to justice but also to foster an environment where victims feel supported and motivated to report. Interviews with legal professionals reveal a consensus on the need for impartial education and the promotion of a culture of respect and equality. It is highlighted that current laws, such as the Comprehensive Organic Criminal Code, are discriminatory by focusing solely on violence against women, and a change in terminology towards "violence against family members" is suggested. This would allow for a more inclusive and equitable treatment of all cases of domestic violence. It would not only contribute to a more just and equitable society, where all members of the family unit are protected and cared for without discrimination.